The effects of alternating heads of state on structural transformation in sub-Saharan Africa - Saturnin Bertrand Nguenda Anya; Fabrice Nzepang (Cogent Economics & Finance)
The objective of this paper is to investigate the effect of alternating heads of state on structural transformation in sub-Saharan Africa (SSA). Indeed, the alternation of a head of state is an institutional tool likely to promote the reallocation of labor, innovation and human capital and thus improve structural change and intra-industry productivity, which are the two components of structural transformation. The primary data collected on the alternation of heads of state, the Africa sector database (ASD) and the World Development Indicators (WDI) allow us to illustrate our remarks using the two steps least squares (2SLS) method on a panel of 17 SSA countries. The results obtained show that the number of alternations of heads of state positively and significantly affects intra-industry productivity and structural change in SSA.